Recent trend in the care of chronic kidney disease patients: A shift from paternalistic to collaborative approach - Suchitra Pal; Santhna Letchmi Panduragan; Faridah Mohd Said (Asian Journal of Medical Sciences, 2024)
The global rise in chronic kidney disease (CKD) necessitates a re-evaluation of healthcare practices. This review explores the shift from paternalistic to collaborative model, focusing on patient empowerment. This article aims to elucidate the foundational concept of patient empowerment, describe the goals of patient-centered care (PCC), identify barriers to PCC implementation, and propose strategies to enhance PCC. The ultimate aim is to empower CKD patients in self-care. The article explores multifaceted strategies of PCC, highlights the pivotal role of shared decision-making, and underscores the necessity of a collaborative clinician-patient partnership. It emphasizes the significance of patient-centered education, benefits of PCC in CKD care, and the role of artificial intelligence in improving healthcare outcomes. This review concludes by summarizing insights into the transformative shift toward patient-centered approaches in CKD management. It emphasizes the positive impact of this paradigm shift on both the healthcare system and CKD patients. The findings highlight the positive effects of PCC on both the health-care system and CKD patients.